2004
DOI: 10.1021/jp037170t
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Sol−Gel TiO2 Thin Films on Various Kinds of Glass Substrates:  The Effects of Na+ and Primary Particle Size

Abstract: To study the effects of ions diffused from the glass substrate on TiO2 photocatalysis, TiO2 thin films were prepared on different kinds of glass substrates at different heating temperatures. The TiO2 films were characterized using X-ray photoemission spectroscopy (XPS), X-ray diffraction (XRD), ellipsometry, and absorption spectroscopy. The photocatalytic activities of the TiO2 thin films were evaluated using the degradation reaction of trichloroethylene (TCE). Diffused ions such as Na+ and Si4+ raised the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 21 publications
5
84
1
1
Order By: Relevance
“…[22][23][24] There have been a number of studies of the photocatalytic oxidation of TCE with TiO 2 under UV irradiation, [1,25,26] and a practical reaction plant has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] There have been a number of studies of the photocatalytic oxidation of TCE with TiO 2 under UV irradiation, [1,25,26] and a practical reaction plant has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was known from the early years of research on photocatalysts that Na diffusion from substrate has an adverse effect on TiO 2 photocatalytic properties, there are few quantitative reported studies. Nam and coworkers studied the effect of Na diffusion on photocatalytic properties of TiO 2 sol-gel films (33) and found that photocatalytic activity is increased with temperature due to the constructive effect of Na on the anatase crystal formation. They also noted that sodium ions cannot be regarded as recombination centers.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic performance is influenced by film characteristics including; composition, bulk and surface structure and nanostructure, atomic to nanoscale roughness, hydroxyl concentration, and impurity concentration (e.g., Fe and Cr) [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%